2020
DOI: 10.1021/acs.inorgchem.0c02241
|View full text |Cite
|
Sign up to set email alerts
|

Cation Distributions and Magnetic Properties of Ferrispinel MgFeMnO4

Abstract: The crystal structure and magnetic properties of the cubic spinel MgFeMnO 4 were studied by using a series of in-house techniques along with large-scale neutron diffraction and muon spin rotation spectroscopy in the temperature range between 1.5 and 500 K. The detailed crystal structure is successfully refined by using a cubic spinel structure described by the space group Fd 3̅ m . Cations within tetrahedral A and octah… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This was because the substitution of Y 3+ ions in place of Fe 3+ ions will disturb the spin cycloid arrangement of the spinel ferrite and thus the ferromagnetic nature gets changed, and so the value of M s increased spontaneously when the concentration of nickel was vigorously increased to 15%. 48 The magnetic behavior of the inverse spinel CFO was dominated by the high spin Fe 3+ ions at tetrahedral sites rather than the Ni 2+ at the octahedral sites, which in turn produced a higher magnetic moment as opposed to that of the octahedral sites. 49,50 The Rietveld refinement cationic distribution, as tabulated in Table 3, showed that the YCFO5 sample displayed the lowest Fe 3+ content in the tetrahedra sites.…”
Section: Magnetic Propertiesmentioning
confidence: 96%
“…This was because the substitution of Y 3+ ions in place of Fe 3+ ions will disturb the spin cycloid arrangement of the spinel ferrite and thus the ferromagnetic nature gets changed, and so the value of M s increased spontaneously when the concentration of nickel was vigorously increased to 15%. 48 The magnetic behavior of the inverse spinel CFO was dominated by the high spin Fe 3+ ions at tetrahedral sites rather than the Ni 2+ at the octahedral sites, which in turn produced a higher magnetic moment as opposed to that of the octahedral sites. 49,50 The Rietveld refinement cationic distribution, as tabulated in Table 3, showed that the YCFO5 sample displayed the lowest Fe 3+ content in the tetrahedra sites.…”
Section: Magnetic Propertiesmentioning
confidence: 96%